AB0204 Serum Levels of Vascular Markers Reflect Disease Severity and Stage in Systemic Sclerosis. (9th June 2015) - Cossu, M.; Andracco, R.; Santaniello, A.; Caronni, M.; Marchini, M.; Severino, A.; Radstake, T.R.; Beretta, L.
Abstract : Background: Vasculopathy is one of the cardinal feature of systemic sclerosis (SSc) that can be observed in every patients from the earliest stages of the disease. Abnormalities in circulating angiogenetic factors and endothelial dysfunction markers in patients at different stages of the disease that include early or non-fibrotic (pre-fibrotic) subjects have not thoroughly described so far. Objectives: To characterize vasculopathy in SSc patients through the determination of 7 selected vascular biomarkers in sera from a large cohort of patients with well defined and distinct clinical characteristics. Methods: Sera from 224 subjects were obtained and concentrations of Angiopoietin 2, CXCL-16, E-Selectin, ICAM-1, IL-8, VCAM-1, VEGF were determined by a Luminex commercial assay. Subjects included 43 healthy controls (HC), 47 early systemic sclerosis patients (EaSSc) according to LeRoy and Medsger criteria (Raynaud's phenomenon + abnormal capillaroscopy patterns and/or SSc-specific antibodies without other signs and symptoms of disease), 48 definitive SSc patients (defSSc) according to the 2013 ACR/EULAR criteria without skin fibrosis, 51 limited cutaneous (lcSSc) and 35 diffuse cutaneous (dcSSc) subjects. Results: The four groups of patients showed well-distinct clinical and laboratory characteristics with a linear trend of decrease in FVC and DLco % predicted levels from EaSSc to defSSc to lcSSc and to dcSSc patients, and a linear trend of increase in CRP, ESR, gamamglobulin serum levels as well as the prevalence of lung fibrosis on the other way around. Serum concentrations of the studied analytes are reported in the table; for most vascular factors a characteristics linear trend (ANOVA polynomial test for trend <0.01) could be observed with the lowest level in HC and a gradual increase that reflects the severity if the disease. Conclusions: Our study demonstrate, for the first time, that circulating levels of vascular involvement start to increase in SSc patients from the earlies stages of the disease when clinical and laboratory findings of advanced disease cannot yet be detected. These abnormalities progress in parallel with the appraisal of the first sclerodermatous manifestation in defSSc and steadly increase with the onset of fibrotic manifestations. Acknowledgements: The present work was financed by a grant from GILS (Gruppo Italiano per la Lotta alla Sclerodermia), theme "La diagnosi precoce della sclerodermia". Disclosure of Interest: None declared